Diagnostic test performance of the Mentzer index in evaluating Saudi children with microcytosis - AlQarni, Amani M.; Althumairi, Arwa; Alkaltham, Nourah K.; AlJishi, Samaa; Hakami, Amani Mohammed; Abdalla, Leena Mohamed Osman Ali; Alawi, Zahra Sayed Jalal; Alreedy, Abdullah H. (Frontiers in Medicine, 2024)
Background: Anemia is a global public health concern, affecting both developing and industrialized countries at a rate of 39.8%. Defined by low hemoglobin concentration, anemia varies in severity based on age: <11 g/dl (6-59 months), <11.5 g/dl (5-11 years), and <12 g/dl (12-14 years).Aim: This study evaluates the Mentzer index's reliability in differentiating iron deficiency anemia from thalassemia trait.Fl) with hemoglobin electrophoresis and iron profile were included. Children with other hematological conditions were excluded.Results: indicate that out of 434 children, 181 were classified as having thalassemia and 345 as having iron deficiency anemia. The Mentzer index showed 74% sensitivity and 63% specificity for beta thalassemia trait, with 61% sensitivity and 36% specificity for iron deficiency anemia. The beta thalassemia trait group had the highest negative predictive value (98%), while iron deficiency anemia had the highest positive predictive value (79%).our study suggests that the Mentzer index is not highly reliable in distinguishing iron deficiency anemia from thalassemia trait among children in Saudi Arabia, aligning with previous literature.